Biosensors Technological Advancement and Their Biomedical, Agricultural, Environmental and Food Industrial Applications: A Review - Tariku Abena (Food, Agriculture and Natural Resources - NETWORKS, 2023)
The biosensors are devices that receive the biological message and convert it into a sensible electrical signal. The biosensing involves a combination of biological entities like DNA, RNA, and proteins/enzymes to the electrochemical transducers. Biosensors comprise a biorecognition element (enzyme, antigen, antibody or nucleic) that mediates selective biocatalysis or specific binding of analyte and transducers that able to measure the signal. There are several types of biosensors being employed today, such as optical, surface plasmon resonance, enzymes, DNA, Phage, and microbial biosensors. Now days biosensor technologies have been employed in biomedicine, food safety standards, defense and environmental monitoring. Detection of the lower or higher limits of glucose in the body, microbial invasion in the body and food, heavy metal detection in soil, water and airborne microbes, pesticides in water and soil and various harmful chemicals produced by body, can be easily and timely monitored with high precision using the different types of biosensors. Biosensors can overcome all the limitation of the traditional methods of chemical and microbiological analyses by offering rapid, non-destructive and affordable methods for quality control. Thus, this review paper highlights biosensor and its components, types of biosensors and its application in different disciplines.